How to Flatter the Laity? Rethinking Catholic Responses to the Reformation (discussiedossier over Catholic Identity and the Revolt of the Netherlands, 1520-1635) - Pollmann, J. (BMGN - Low Countries Historical Review, 2011)
This rejoinder summarises the two main questions which Catholic Identity and the Revolt of the Netherlands, 1520-1635 seeks to address, and explains the way in which the author approached these before engaging with the points raised by the three reviewers. Noting the reviewers’ appreciation for the book’s emphasis on the experience of the laity and their role in the Catholic revival, the rejoinder discusses the points of criticism they raised, as well as the potential for further research. Encouraging the reader not to be deceived by the smokescreen of uniformity and hierarchy which the post-Tridentine Catholic Church has drawn up, the author suggests that we can account much more satisfactorily for the curious changes in fortune of the Catholic Church by looking beyond institutional sources, by appreciating the virtues of fragmentation and by broadening our scope to the whole of the religious landscape. This response is part of the discussion forum 'Catholic Identity and the Revolt of the Netherlands 1520-1635' (Judith Pollmann).